Deployment of Sensors to Optimize the Network Coverage Using Genetic Algorithm - Fozia Hanif Khan; Rehan Shams; M. Umair; M. Waseem (Sir Syed University Research Journal of Engineering and Technology, 2012)
Wireless Sensor Networks (WSNs) are commonly used in various pervasive applications. Wireless communication is the fastest growing segment of the communication industry that has captured attention of the media and imagination of the public. The purpose of this study is to develop a Genetic algorithm that provides a proper deployment of sensors in order to optimize the coverage problem. The genetic algorithm optimizes the operational modes of sensors nodes for transmitting signals. In this paper we will present the optimum method for the mobile sensors nodes placement, so that transmission of signals and the field coverage can be improved. One of the critical issues of today’s world is to ensure that the quality of services requirement is at an acceptable level and genetic algorithm give the best solution for the above discussed problem. The algorithm has been implemented in MATLAB using its genetic algorithm tool box along with the custom code.